Editorial: The Role of Eye Movements in Sports and Active Living - Barbieri, Fabio Augusto [UNESP]; Rodrigues, Sergio Tosi [UNESP] (Frontiers Media Sa, 2020)
& nbsp;& nbsp;
Keywords: visual information; sports context; gaze behavior; movement control; eye-tracking